2019
DOI: 10.1177/0972753120911840
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic Nerve Structural and Functional Recovery with Extract of Phyllanthus amarus and Esculetin in STZ-Induced Hyperglycemic Rats

Abstract: Background: Diabetes-instigated nerve damage is a chronic complication including impaired peripheral nerve function with lowered nerve conduction velocity (NCV), demyelination of nerve fibres and alterations in the behaviour. Many clinical and experimental studies have proved that Phyllanthus amarus and esculetin have potential effects against various diseases. Purpose: The aim of this study is to assess the neuroprotective role of hydro-ethanolic extract of Phyllanthus amaras (PAE) and esculetin (ESC) on NCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Prabakaran et al [ 91 ] found that oral administration of esculetin (10–40 mg/kg) significantly reduced blood glucose levels and increased plasma insulin levels in diabetic rats, and ameliorated diabetes-induced tissue damage in the liver and kidney by attenuating hyperglycemia-mediated oxidative stress. Furthermore, esculetin has been demonstrated to have protective effects against diabetes-induced complications such as nerve damage, [ 92 ] and vascular dysfunction. [ 93 ]…”
Section: Pharmacological Activities Of Esculetinmentioning
confidence: 99%
“…Prabakaran et al [ 91 ] found that oral administration of esculetin (10–40 mg/kg) significantly reduced blood glucose levels and increased plasma insulin levels in diabetic rats, and ameliorated diabetes-induced tissue damage in the liver and kidney by attenuating hyperglycemia-mediated oxidative stress. Furthermore, esculetin has been demonstrated to have protective effects against diabetes-induced complications such as nerve damage, [ 92 ] and vascular dysfunction. [ 93 ]…”
Section: Pharmacological Activities Of Esculetinmentioning
confidence: 99%
“…The effects of esculetin on numerous cancer cell types have been extensively studied ( 94 , 321 342 , 519 , 524 , 525 ) and are the basis for efforts to develop novel therapeutics ( 98 , 341 ). Neuroprotective and behavioral actions of esculetin have also been described ( 111 , 299 , 367 371 , 526 528 ). Selected publications highlighting these effects of esculetin are featured in Table 3 .…”
Section: Effects Of Bioactive Compounds Found In a Scopariamentioning
confidence: 99%